Moccasin Tracks: Reading the Narrative in Traditional Indigenous Craft Work ... - Anton, James Wyatt (Arts, 2018)
The colonization of Canada has produced deleterious effects for the First Nations peoples that originally inhabited the land. Through sharing stories with a number of First Nations craft producers the objective of this research was to capture the endurance of First Nations culture beyond the disastrous effects of colonization and repression faced by the First Peoples of this continent. This study investigates the production of craft goods in First Nations communities by building on the concept of the narrative embedded in the material craft culture. By narrative, this study refers to the culturally specific ways that stories are created and maintained to preserve elements of culture and society. Craft goods continue to be produced and used in these communities as a way of preserving and reproducing the specific tribal knowledges that exist within these groups. Data in this project comes from semi-structured interviews with Indigenous craft makers. The methodology was developed to confront the positionality ...